2021
DOI: 10.1590/1984-6487.sess.2021.37.e21202a
|View full text |Cite
|
Sign up to set email alerts
|

Pandemia de covid-19 e população LGBTI+. ( In)visibilidades dos impactos sociais

Abstract: Resumo O objetivo do artigo é refletir criticamente sobre os impactos sociais da pandemia de covid-19 e as medidas de enfrentamento no cotidiano de Lésbicas, Gays, Bissexuais, Transgênero, Intersexuais e outras identidades (LGBTI+) no contexto brasileiro. Inicialmente é realizado um resgate histórico das necessidades sociais e de saúde que pessoas LGBTI+, evidenciando a importância da compreensão da LGBTIfobia como um determinante social da saúde, além de retomar alguns marcos que resultaram na criação e imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…These studies also recognized that the crisis is possibly affecting diverse gender identities [ 26 ] and that there is a need for intersectional data collection beyond a binary view [ 23 ] ( Table 1 ). We found a gender-diverse approach in only six papers whose analysis focused on people of different gender identities [ 36 , 49 , 56 , 61 , 67 , 70 ]. We also found studies that only superficially mentioned LGBTIQ+ groups [ 22 , 34 , 39 , 50 , 52 , 54 , 58 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies also recognized that the crisis is possibly affecting diverse gender identities [ 26 ] and that there is a need for intersectional data collection beyond a binary view [ 23 ] ( Table 1 ). We found a gender-diverse approach in only six papers whose analysis focused on people of different gender identities [ 36 , 49 , 56 , 61 , 67 , 70 ]. We also found studies that only superficially mentioned LGBTIQ+ groups [ 22 , 34 , 39 , 50 , 52 , 54 , 58 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rieger et al [ 22 ] enunciated elements related to gender diversity, indicating that most survivors of gender-based violence are women and gender-diverse people. Different studies in Brazil, India, and Indonesia indicated psychological distress or mental health problems in gender-diverse persons during the pandemic, social distancing, and lockdown periods [ 49 , 61 , 67 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Desse modo, conforme a emergência de combater a invisibilidade Trans 12 , esse projeto se apropriou do âmbito virtual como veículo de empoderamento e apoio à essa parcela social. A educação em saúde é promovida a partir do entendimento do indivíduo em sua integralidade, não apenas valorizando o corpo físico, mas sua cidadania e a conscientização de direitos para sua garantia.…”
Section: Criação Do Transligadounclassified